Enhancing natural killer cell-mediated lysis of lymphoma cells by combining therapeutic antibodies with CD20-specific immunoligands engaging NKG2D or NKp30. (2nd January 2016) - Kellner, Christian; Günther, Andreas; Humpe, Andreas; Repp, Roland; Klausz, Katja; Derer, Stefanie; Valerius, Thomas; Ritgen, Matthias; Brüggemann, Monika; van de Winkel, Jan GJ; Parren, Paul WHI; Kneba, Michael; et al.
Abstract : Antibody-dependent cell-mediated cytotoxicity (ADCC) mediated through the IgG Fc receptor FcγRIIIa represents a major effector function of many therapeutic antibodies. In an attempt to further enhance natural killer (NK) cell-mediated ADCC, we combined therapeutic antibodies against CD20 and CD38 with recombinant immunoligands against the stimulatory NK cell receptors NKG2D or NKp30. These immunoligands, respectively designated as ULBP2:7D8 and B7-H6:7D8, contained the CD20 scFv 7D8 as a targeting moiety and a cognate ligand for either NKG2D or NKp30 (i.e. ULBP2 and B7-H6, respectively). Both the immunoligands synergistically augmented ADCC in combination with the CD20 antibody rituximab and the CD38 antibody daratumumab. Combinations with ULBP2:7D8 resulted in higher cytotoxicity compared to combinations with B7-H6:7D8, suggesting that coligation of FcγRIIIa with NKG2D triggered NK cells more efficiently than with NKp30. Addition of B7-H6:7D8 to ULBP2:7D8 and rituximab in a triple combination did not further increase the extent of tumor cell lysis. Importantly, immunoligand-mediated enhancement of ADCC was also observed for tumor cells and autologous NK cells from patients with hematologic malignancies, in which, again, ULBP2:7D8 was particularly active. In summary, co-targeting of NKG2D was more effective in promoting rituximab or daratumumab-mediated ADCC by NK cells than co-ligation of NKp30. The observed increase in the ADCC activity of these therapeutic antibodies suggests promise for a 'dual-dual-targeting' approach in which tumor cell surface antigens are targeted in concert with two distinct activating NK cell receptors (i.e. FcγRIIIa and NKG2D or B7-H6).